KARAKTERISTIK SIFAT FISIKA TANAH ULTISOL AKIBAT PEMBERIAN BIOCHAR BERBAHAN BAKU SISA TANAMAN KELAPA SAWIT - Abdul Rauf; Supriadi Supriadi; Fitra Sawal Harahap; Makruf Wicaksono (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2020)
The physical characteristics of ultisols due to the provision of biochar made from palm oil plant residue aims to determine the effect of giving various biochar made from oil palm plant residues on the physical properties of Ultisols. The research design used completely randomized design, consisting of 5 treatments, namely K = without giving biochar, BB = oil palm stem biochar, BP = oil palm frond biochar, BT = oil palm empty bunches biochar and BK = combination of biochar ingredients. Each treatment was repeated 4 times, so that the number of experimental units became 20 units. The parameters observed included soil density, soil porosity, soil texture, soil permeability and available water. The results showed that giving biochar significantly decreased the bulk weight and significantly increased the soil porosity of Ultisols.Key words : biochar, oil palm wastes, physical properties of soil and ultisol